The Impact of Cash on Delivery Feature on Customer Satisfaction and Repurchase Intention on the Shopee Platform in Pontianak City - Hawari, Delvin; Fachri, Helman (UNIVERSITAS PAKUAN, 2025)
The rapid growth of online transactions through e-commerce platforms has prompted service providers to offer secure and convenient payment methods, one of which is the Cash On Delivery (COD) feature. This study aims to determine the influence of the COD feature on customer satisfaction and repurchase intention among Shopee users in Pontianak City, as well as to answer whether customer satisfaction mediates this relationship. The research method employed a quantitative associative design with data collected through a questionnaire administered to 150 Shopee users who utilized COD. The data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results indicate that the COD feature significantly enhances customer satisfaction, which in turn positively influences repurchase intention. However, the direct effect of COD on repurchase intention is not significant without the mediation of customer satisfaction. These findings reinforce the understanding that customer satisfaction is a key factor in enhancing loyalty through practical and secure payment methods. In conclusion, the development of optimal COD features can improve customer retention, and further research is recommended to explore other factors that can strengthen repurchase intention on e-commerce platforms.